Kiat Ayah Membangun Pemahaman Moderasi Beragama Di Keluarga Kristiani - Manurung, Kosma (Jurnal Ap-Kain, 2025)
Religious moderation upholds human dignity. It is believed that through religious moderation, societal harmony will be established, national unity will be strengthened, and the values of Pancasila will be practiced in daily life, including in the context of religious life. Given the importance of religious moderation, it is necessary to teach it within the family. This article seeks to describe fathers' tips for developing an understanding of religious moderation in Christian families. Through the use of descriptive qualitative methods and elaborating on literature reviews, it is hoped that it will provide a strong, systematic, and in-depth picture related to Christianity and public life, the importance of religious moderation, and fathers' tips for developing an understanding of religious moderation in Christian families. It is concluded that a father will maximize the development of an understanding of religious moderation in a Christian family when he introduces religious moderation to his children from an early age, builds an ecosystem, becomes a practice partner for his children, and becomes a role model in religious moderation himself.AbstrakModerasi beragama menjunjung tinggi harkat dan martabat kemanusiaan. Melalui moderasi beragama diyakini keharmonisan masyarakat akan terbentuk, persatuan dan kesatuan bangsa semakin dipererat, serta nilai-nilai Pancasila teramalkan dalam praktik keseharian hidup termasuk juga dalam konteks kehidupan beragama. Mengingat begitu pentingnya moderasi beragama ini, maka perlu untuk diajarkan hingga pada tatanan keluarga. Adapun artikel ini berupaya untuk menjabarkan kiat ayah dalam membangun pemahaman moderasi beragama di kelaurga Kristiani. Melalui penggunaan metode kualitatif deskriptif dan mengelaborasikannya dengan kajian literatur diharapkan mampu memberikan gambaran yang kuat, tersistimatik, serta mendalam terkait dengan kekristenan dan kehidupan publik, arti penting moderasi beragama, juga kiat ayah membangun pemahaman moderasi beragama di keluarga Kristiani. Disimpulkan seorang ayah akan maksimal membangung pemahaman moderasi beragama di keluarga Kristiani ketika sang ayah memperkenalkan moderasi beragama sedari awal pada anak-anaknya, membangun ekosistem, menjadi teman latihan anak, serta menjadi dirinya role model dalam moderasi beragama.